THE USE OF LOCAL HERBAL IN ALTERNATIVE AND COMPLEMENTARY THERAPIES AS MIDWIFERY CARE SYNERGISTIC THERAPY IN SASAK ETHNIC - Triandini, I Gusti Agung Ayu Hari; Hairani, Hairani (Universitas Pendidikan Mandalika, 2024)
Traditional healers are still the main choice of the Sasak tribe to assist with childbirth. The city of Mataram ranks second lowest in terms of the percentage of births assisted by health workers and the third lowest in the West Nusa Tenggara region in terms of the percentage of births in health service facilities because of holistic service experience, culture, education, and outreach to health facilities factors. Traditional health services have been proven for a long time and are used by the community in preventive, promotive, curative, and rehabilitative efforts. This is very useful, especially in areas where access to health services is limited. The term